Proximal and Distal Failure Site Analysis in Percutaneous Achilles Tendon Rupture Repair. Issue 4 (16th October 2019) - Wagner, Pablo; Wagner, Emilio; Lopez, Mario; Etchevers, Gaston; Valencia, Oscar; Guzman-Venegas, Rodrigo
Category: Ankle Introduction/Purpose: Different techniques have been described for Achilles Tendon Rupture repair, but no biomechanical evaluation have been performed separately for proximal and distal suturing techniques.The purpose of this study was to biomechanically analyze 3 proximal and 2 distal suture configurations during a simulated cyclic load and load to failure. It was hypothesized that proximal suturing technique was stronger than the distal one and that the modified double suturing technique was the strongest of all techniques. Methods: A simulated, mid-substance rupture was created 6 cm proximal to the calcaneal insertion in 15 fresh-frozen cadaveric Achilles tendons, obtaining 15 proximal and 12 distal samples. Specimens were tested independently and randomly allocated to different suture techniques: proximal fixation site groups: (A1) classic Dresden technique, (A2) modified Dresden, (A3) double modified Dresden; distal fixation groups: (B1) classic distal suture and (B2) modified distal suture. Repairs were subjected to a cyclic testing (1000 cycles of 50-200 N) and load to failure. Load to failure, cause of failure and tendon elongation was evaluated. Fischer's test was used as statistical analysis. Results: None of the proximal tendon and 7/12 of the distal samples failed in cyclic testing. The proximal fixation groups demonstrated significantly more strength than the distal groups (p< 0.05) with average failure loads of 598 N, 587 N and 710 N for groups A1, A2 and A3 respectively (A3 stronger than A1 and A2, p=0, 035). Groups B1 and B2 failed on average at 416 N and 351 N respectively, p=0.24. The majority of all repairs failed in the suture- tendon interphase.Regarding elongation, no significant differences were found between groups (p=0.57). Conclusion: The distal fixation site in the Dresden percutaneous Achilles tendon repair is weaker than the proximal fixation site. A proximal modified suture configuration increased resistance to cyclic loading and load to failure significantly. A modification in the proximal and distal fixation sites can be suggested to improve repair strength and hopefully achieve a better outcome.